Implementasi Keterampilan Berbicara Menggunakan Metode Sosiodrama pada Mata Pelajaran PAI di SDN 09 Paninggahan Kabupaten Solok - Bambang Irwanto; Jasmienti Jasmienti; Al Baihaiqi Anas; Alimir Alimir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The background to this research is that the speaking skills of grade 4 students are still lacking because many students are still embarrassed to answer questions given by the teacher and are also lazy to express opinions during lesson discussions and when called to come forward, they are asked questions and do not want to answer. Apart from that, speaking fluency, accuracy of word choice, sentence structure, logic or reasoning and communicativeness or eye contact are still relatively low. The aim of this research is to determine the implementation of speaking skills using the sociodrama method and to determine the factors inhibiting the use of the implementation of speaking skills using the sociodrama method in PAI subjects at SD N 09 Paninggahan. This research uses a qualitative approach. With data collection techniques through observation and interviews. The key informants are class IV students and the supporting informants are PAI teachers and class teachers. Data analysis in this research involves data reduction, data display, and then conclusions. Based on the research results, it was found: (1) The implementation of students' speaking skills using the sociodrama method in PAI subjects at SDN 09 Paninggahan, Solok Regency has been implemented well. This shows that in sociodrama students are fluent in speaking, students are precise in choosing words, students are in sentence structure. sociodrama is categorized as very good, students' logic and reasoning are also very good, and students' communicativeness and eye contact. (2) Factors Inhibiting Students' Speaking Skills Using the Sociodrama Method in PAI Subjects at SD N 09 Paninggahan, Solok Regency include students experiencing concentration problems, fear of making mistakes, shame and lack of self-motivation, but the most dominant is that students feel afraid of doing mistakes due to nervousness.